The Study on the Characteristics of Pressure Arch above the Twin-Parallel Openings in the Jointed Rock Masses - Kunpeng Gao; Kang Liang; Leyao Wang; Changhao Li; Jinghai Yu; Runyi Wu (Advances in Civil Engineering)
The self-bearing capacity of the rock masses has been a hot pot in the research of supporting technology in underground engineering. The pressure arch has been considered the main hypothesis to explain the self-bearing capacity of the rock masses. In this paper, the engineering of the twin-parallel openings in the jointed rock masses was selected as the background of the research. The characteristics of the deformation or the movement of the rock masses above the openings were studied based on the pressure arch theory. The difference between the single opening and the twin-parallel openings has been revealed, and the mechanism has also been illustrated. Besides, the joints’ strength, the in situ stress ratio, the distance between the two openings, and the excavation sequence were selected as the variable parameters, and their influences have also been illustrated by the DEM method.